TIPE2 regulates periodontal inflammation by inhibiting NF-κB p65 phosphorylation - Yanmei DU; Xiaohua LIU; Changjie XIAO; Jianbin LI; Zhenxian SHENG; Yuxin WANG; Ronglin WANG; Xijiao YU (University of São Paulo, 2023)
Abstract The roles and molecular mechanisms of tumor necrosis factor-α-induced protein 8-like 2 (TIPE2) in periodontitis remain largely unknown. Objective This study aimed to determine the expression of TIPE2 and NF-κB p65 in rat Porphyromonas gingivalis-induced periodontics in vivo. Methodology Periodontal inflammation and alveolar bone resorption were analyzed using western blotting, micro-computed tomography, TRAP staining, immunohistochemistry, and immunofluorescence. THP-1 monocytes were stimulated using 1 μg/ml Pg. lipopolysaccharide (Pg.LPS) to determine the expression of TIPE2 in vitro. TIPE2 mRNA was suppressed by siRNA transfection, and the transfection efficiency was proven using western blotting and real-time PCR. The NF-κB pathway was activated by treating the cells with 1 μg/ml Pg.LPS to explore related mechanisms. Results The expression of both TIPE2 and NF-κB p65 was increased in the gingival tissues of rat periodontitis compared with normal tissues. Positive expression of TIPE2 was distributed in inflammatory infiltrating cells and osteoclasts in the marginal lacunae of the alveolar bone. However, strong positive expression of TIPE2 in THP-1 was downregulated after Pg.LPS stimulation. TIPE2 levels negatively correlated with TNF-α and IL-1β. Decreased TIPE2 in THP-1 further promoted NF-κB p65 phosphorylation. Mechanistically, TIPE2 knockdown upregulated NF-κB signaling pathway activity. Conclusions Taken together, these findings demonstrate that TIPE2 knockdown aggravates periodontal inflammatory infiltration via NF-κB pathway. Interventions aimed at increasing TIPE2 may help in the therapeutic applications for periodontitis.